Establish Growth Curve in Light of Body Mass Index for Infertile Women in Baghdad City - ghafil, Hawraa; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2013)
Objective: To establish growth curve for a sample of infertile women and to assess Body Mass Index. Methodology: Non-probability (purposive sample) of (100) infertile women, who visit Kamal Al-Samaraee Hospital/ fertility and IVF center . The data are collected through the use of constructed questionnaire, which consists of two parts. Part 1: consists of (5) items about demographic characteristics, part 2: consists of (4) items about reproductive status, descriptive statistical analysis procedures (frequency, percentage, Contingency coefficients, polynomial cube order). Results: Revealed that the infertile women in the study group had decrease in their Body Mass Index with aging (with increase of infertility duration) and that related to their knowledge about the effect of obesity on their condition and decrease the chance for pregnancy and reproduction. Recommendations: the study recommended that all the infertile women should be maintenance their weight and become within normal rang to avoid the infertility due to obesity.